2006
DOI: 10.1111/j.1365-2699.2006.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Environment, dispersal and patterns of species similarity

Abstract: Explaining patterns of spatial variation in species composition is a major challenge facing ecologists. While many studies have focused on patterns of species richness and their causal factors, the spatial change in species composition has received far less attention (but see Harrison et al. ABSTRACTAim The aim of this paper is to evaluate the combined effects of geographical distance and environmental distance on patterns of species similarity (similarity in species composition between sites), and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
135
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 40 publications
14
135
1
2
Order By: Relevance
“…Accordingly, several studies have demonstrated a host of different factors that may influence variation of species composition through space: (1) spatial and environmental gradients (e.g. Clark et al, 1999;Nekola & White, 1999;Oliveira-Filho & Fontes, 2000;Carneiro & Valeriano, 2003;Steinitz et al, 2006Steinitz et al, , 2007bLegendre et al, 2009); (2) differences in the physiology, in the degree of biological interactions and in the dispersal ability of the species (Nekola & White, 1999;Tuomisto et al, 2003;Gilbert & Lechowicz, 2004); (3) barriers imposed by the configuration of the landscape and the influence of weather on species' dispersion (Nekola & White, 1999;Hubbel, 2001); (4) stochastic processes generated randomly and independently of environmental dissimilarities (Neutral Theory sensu Hubbel, 2001;Soininen et al, 2007b;Steinbauer et al, 2012); (5) species' tolerance to fragmentation (Arroyo-Rodríguez et al, 2013); (6) spatial scale (extension, resolution; Nekola & White, 1999;Steinitz et al, 2006;Soininen et al, 2007b;Arroyo-Rodríguez et al, 2013). Therefore, more accurate analysis involving other variables could yield further explanations regarding the spatial distribution observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, several studies have demonstrated a host of different factors that may influence variation of species composition through space: (1) spatial and environmental gradients (e.g. Clark et al, 1999;Nekola & White, 1999;Oliveira-Filho & Fontes, 2000;Carneiro & Valeriano, 2003;Steinitz et al, 2006Steinitz et al, , 2007bLegendre et al, 2009); (2) differences in the physiology, in the degree of biological interactions and in the dispersal ability of the species (Nekola & White, 1999;Tuomisto et al, 2003;Gilbert & Lechowicz, 2004); (3) barriers imposed by the configuration of the landscape and the influence of weather on species' dispersion (Nekola & White, 1999;Hubbel, 2001); (4) stochastic processes generated randomly and independently of environmental dissimilarities (Neutral Theory sensu Hubbel, 2001;Soininen et al, 2007b;Steinbauer et al, 2012); (5) species' tolerance to fragmentation (Arroyo-Rodríguez et al, 2013); (6) spatial scale (extension, resolution; Nekola & White, 1999;Steinitz et al, 2006;Soininen et al, 2007b;Arroyo-Rodríguez et al, 2013). Therefore, more accurate analysis involving other variables could yield further explanations regarding the spatial distribution observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Such relation is partially due to the spatial autocorrelation pattern of environmental variables, with closer locations tending to be more environmentally similar to each other (Legendre, 1993), which, by itself, influences the composition of species communities (Harrison et al, 1992;Jiménez-Valverde et al, 2010). Therefore, a decrease in the similarity of environmental conditions along space may result in a correspondent decrease of the similarity in species composition (Steinitz et al, 2006).…”
Section: Palavras-chavementioning
confidence: 99%
See 1 more Smart Citation
“…For multivariate data Mantel correlograms can be applied (Legendre & Legendre 1998;Sokal & Rohlf 1981). A simple possibility for vegetation data is to regress similarity of units regarding species composition against their geographical separation (Nekola and White, 1999;Steinitz et al, 2006). To test for the influence of different vegetation types on patterns of compositional similarity data was divided into subsets.…”
Section: Distance Decaymentioning
confidence: 99%
“…Here, we investigate the distance decay of compositional similarity whilst accounting for the change of the relationship between compositional similarity and its drivers with geographical distance between plots. Steinitz et al, (2006) highlight that the studies are limited to which extent patterns of distance decay depend on the position along environmental gradients. Accordingly Jones et al, (2006) emphasize that explanatory power of variables might increase with the length of the gradient covered.…”
Section: Introductionmentioning
confidence: 99%